Positive Youth Development - Lerner, Richard M.; Lerner, Jacqueline V.; Benson, Janette B., 1956- (Advances in child development and behavior ;, 2011)
Each chapter provides in-depth discussions and this volume serves as an invaluable resource for Developmental or educational psychology researchers, scholars, and students. Includes chapters that highlight some of the most recent research in the area of Positive Youth Development. Each chapter provides in-depth discussions. An invaluable resource for Developmental or educational psychology researchers, scholars, and students.